Regulation of the sperm acrosome reaction - Savaria, Julie (University of Ottawa (Canada), 2009)
The acrosome is a large secretory granule that undergoes exocytosis when receptors on the sperm surface bind ligands found on the oocyte's extracellular matrix. Acrosomal exocytosis resembles stimulated neurotransmitter release in neurons in that it is triggered by a rise in intracellular calcium. In neurons, a core complex composed of the SNARE proteins - syntaxin, SNAP-25 and VAMP is involved in synaptic vesicle fusion. Regulation of this protein complex is accomplished through the action of accessory proteins, including complexin, which is thought to stabilize the core SNARE complex prior to fusion. Recent evidence has revealed that isoforms of the SNARE proteins and their accessory proteins are present in mammalian sperm, where they might mediate the exocytosis of the acrosome. It has been hypothesized that the SNARE complex may be regulated as part of the process of capacitation, a set of physiological changes that occur within the female tract, during which the spermatozoon acquires its fertilizing ability. In this thesis, the hypothesis that complexin is involved in the regulation of the acrosome reaction is examined. To do so, streptolysin-O permeabilized sperm will be used to study the effect of recombinant complexin and of an antibody directed against complexin on the rate of the acrosome reaction, as well as on the sensitivity of this fusion machinery to calcium. Regulation may also occur through posttranslational modification or conformational change in one of the SNARE proteins. Syntaxin 2, which is the isoform present in sperm, showed a shift in apparent molecular weight on Western blots with capacitation. Alkaline carbonate extraction and dephosphorylation were used in an attempt to determine the kind of modification syntaxin 2 is undergoing during capacitation. Together, these data will shed light onto the role of complexin in the regulation of the acrosome reactions as well as on the modifications syntaxin 2 undergoes during capacitation.
Keywords: Biology, Molecular.